2013
DOI: 10.1681/asn.2012060628
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Insulin Receptor in the Proximal Tubule Promotes Hyperglycemia

Abstract: Nearly all renal tubular epithelial cells express insulin receptor. The insulin receptor in the distal tubule appears to modulate BP, but the role of the insulin receptor in the proximal tubule is unknown. Here, we selectively knocked out the insulin receptor from the proximal tubules of mice. Western blotting confirmed a two-to three-fold reduction in renal cortical homogenate insulin receptor-b among knockout mice compared with wild-type littermates. Young knockout mice exhibited a mildly diabetic phenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 33 publications
7
88
0
1
Order By: Relevance
“…An increase in gluconeogenesis, and hence, PEPCK activity, generates additional HCO 3 − exported by the proximal tubule to raise blood pH during metabolic acidosis (Curthoys and Moe, 2014). Deletion of the insulin receptor in tubule epithelium induces systemic hyperglycemia in the mouse (Tiwari et al, 2013). Increased glucose uptake under high glucose and high insulin conditions result in increased glycogen deposition (Gerich et al, 2001) and a reduction in fatty acid oxidation in the cortex (Meyer et al, 1997).…”
Section: Adipocyte Communication Maintains Systemic Glucose Homeostasismentioning
confidence: 99%
“…An increase in gluconeogenesis, and hence, PEPCK activity, generates additional HCO 3 − exported by the proximal tubule to raise blood pH during metabolic acidosis (Curthoys and Moe, 2014). Deletion of the insulin receptor in tubule epithelium induces systemic hyperglycemia in the mouse (Tiwari et al, 2013). Increased glucose uptake under high glucose and high insulin conditions result in increased glycogen deposition (Gerich et al, 2001) and a reduction in fatty acid oxidation in the cortex (Meyer et al, 1997).…”
Section: Adipocyte Communication Maintains Systemic Glucose Homeostasismentioning
confidence: 99%
“…Indeed Mima, et al 18 have shown in models of both type 1 and type 2 diabetes that glomerular insulin signaling is lost early in disease progression. Conversely, insulin signaling in the tubular compartment, which controls ion reabsorption from the filtrate, as well as blood pressure and systemic glucose control 19 are not affected. Compelling evidence from human studies shows that systemic insulin resistance is associated with proteinuric kidney disease in non-diabetic patients 20 and that, in the setting of diabetes, insulin resistance predicts those patients who will develop nephropathy in both type 1 21-23 and type 2 diabetes 24 .…”
Section: Podocyte Signaling Pathways In Dkdmentioning
confidence: 99%
“…Total RNA (500 ng) from rat Kidney cortex was subjected to RT-qPCR using SYBR-green PCR Master Mix (Applied Biosystems) as described previously7475767778 qPCRs using SYBR green reagent with gene-specific primers and GAPDH gene primers (internal control). The gene specific primers for rat were: E-cadherin- GCCCAGGAAATACACCCCTC (F) and ACTCAGGTCCAAATCAGCCG (R); collagen IVα- GGAGAACAAGGGGTCAGTGG (F) and TCCTGTTGGGGCAAAGTCTC (R); fibronectin- CCTGTGTTCTCCCGTTTCACT (F) and TGTGCTACACCACAGATGTCC (R); TGF-β- TCCCAACTACAGAAAAGCAGTCA (F) and GCAATGCAGACGAAGCAGAC (R); IL6- CCCAACTTCCAATGCTCTCCT (F) and GGATGGTCTTGGTCCTTAGCC (R); IL-18- GAACTGAGCCCCTCCCTACTA (F) and TGTCTTCAATCCATCCCAGAGC (R); MMP-2- AAGGATGGAGGCACGATTGG (F) and GGGAACTTGATGATGGGCGA (R); MMP-9- ATGGTTTCTGCCCCAGTGAG (F) and CCTTTAGTGGTGCAGGCAGA (R); RAGE-GAGGATGAGGGCATCTACAGC (F) and TCACCGGTTTCTGTGACCC (R), and GAPDH gene primers (AGGTCGGTGTGAACGGATTTG(F) and TGTAGACCATGTAGTTGAGGTCA (R).…”
Section: Methodsmentioning
confidence: 99%
“…Protein levels from rat kidney cortex homogenates and from cell lysates were quantitated using immunoblotting as described by us previously7374757677787980. The antibodies against HDACs (Cell signalling technology, MA USA), E-cadherin, Fibronectin, Collagen, RAGE (Santa Cruz Biotechnology, USA), TGF-beta, Histone H3, acetyl Histone H3 (Abcam MA USA) and anti-acetyl Histone H4 (Millipore) and, anti-β-actin (Cell signalling technology, MA USA) were used and signals were detected using a chemi-luminiscence-based detection system (Amersham).…”
Section: Methodsmentioning
confidence: 99%